Understanding the contrast mechanism in Scanning Tunneling Microscopy (STM) images of an intermixed tetraphenylporphyrin layer on Ag(111) - Comanici, Karmen; Buchner, Florian; Flechtner, Ken; Lukasczyk, Thomas; Gottfried, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2008)
The appearance of tetraphenylporphyrins in scanning tunneling micrographs depends strongly on the applied bias voltage. Here, we report the observation and identification of certain features in scanning tunneling microscopy (STM) images of intermixed layers of tetraphenylporphyrin (2HTPP) and cobalt-tetraphenylporphyrin (CoTPP) on Ag(111). A significant fraction of an ordered monolayer of commercially available CoTPP appears as "pits" at negative bias voltages around - 1 V. The obvious possibility that these pits are missing molecules within the ordered layer could be ruled out by imaging the molecules at reduced bias voltages, at which the contrast of the pits fades, and at positive bias voltages around +1 V, at which the image contrast is inverted. With the investigation of the electronic structure, in particular the density of states (DOS) close to the Fermi level, of CoTPP and 2HTPP layers by means of ultraviolet photoelectron spectroscopy (UPS) and scanning tunneling spectroscopy (STS), the contrast mechanism was clarified. The correlation of the bias dependent contrast with the UPS data enabled us to interpret the"pits" as individual 2HTPP molecules. Additional evidence could be provided by imaging layers of different mixtures of 2HTPP and CoTPP and by high-resolution STM imaging of the features in CoTPP. © 2008 American Chemical Society.